Comparative Gastro-Protective Effects of Nigella sativa (Kalojira) and Omeprazole against Aspirin Induced Gastric Ulcer in Albino Rats (Delta Medical College Journal, 2016)
Background: Nigella sativa seeds have been in use as a natural remedy for over thousands of years in various parts of the world. These seeds are reported to have beneficial effects almost on every system of the body.Objective: To evaluate the gastro-protective effect of Nigella sativa on aspirin induced gastric ulcer with comparison to omeprazole.Materials and method: This experimental study was carried out in the department of Pharmacology and Therapeutics, Dhaka Medical College, Dhaka, Bangladesh in collaboration with the department of Pathology, Delta Medical College, Dhaka, Bangladesh. A total number of 30 healthy albino rats were used in this study. The experiment was divided into 2 parts: Experiment-1 and Experiment-2. Experiment-1 comprised of 12 rats: Group-A and Group-B having 6 rats in each group. Ulcer was produced by administration of aqueous suspension of aspirin (200 mg/kg body wt) in Group-B where Group-A served as control and was provided with normal saline (2 ml/kg body wt). All the rats were sacrificed after 4 hrs to confirm gastric ulcer by histopathology. Experiment-2 comprised of 18 rats: Group-C, Group-D and Group-E having 6 rats in each group. Group-C served as disease control group and provided with normal saline (2 ml/kg body wt). Group-D was provided with alcoholic extract of Nigella sativa (150 mg/kg body wt) and Group-E was provided with omeprazole suspension (20 mg/kg body wt). After 8 days of treatment, animals were fasted for 24 hrs. Then aqueous suspension of aspirin (200 mg/kg body wt) was administered and after 4 hrs all rats were sacrificed. Gross and microscopic examinations were performed to evaluate the results.Results: Aspirin caused marked gastric damage in negative control group which was prevented in omeprazole suspension and Nigella sativa extract treated groups significantly. The protective effect was maximum with omeprazole followed by alcoholic extract of Nigella sativa.Conclusion: Alcoholic extract of Nigella sativa showed significant protection against aspirin induced gastric ulcer in rats as compared to omeprazole.Delta Med Col J. Jul 2016 4(2): 61-66